Prevalensi Penyakit Paru Obstruktif Kronik Pada Penyapu Jalan Raya di Jakarta - Susanto, Agus Dwi; Antono, Wahyu; Yunus, Faisal (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Background: Chronic obstructive pulmonary disease (COPD) is an important disease worldwide in both high-income and low-income countries. Dust has been known to increase COPD risk. During sweeping activity, sweepers are exposed to dust. The street sweepers are exposed to dust particles, bioaerosols, and various harmful gases. In this study we evaluates the prevalence of COPD among street sweepers in Jakarta Method: This is a cross-sectional study among 153 street sweepers in Jakarta, Indonesia with age more than 40 years old with working period more than 2 years. Subjects were collected by cluster sampling method based on working location correlated with Jakarta regional district area. COPD was diagnosed by using questionnaires of COPD Assessment Test (CAT), The Modified British Medical Research Council (mMRC), spirometry examination based on Pneumobile Project Indonesia, and bronchodilator test if there was obstructive results. Results: A total of 153 subjects was selected for spirometry examination. The prevalence of COPD among street sweepers in Jakarta, Indonesia was 10 of 153 subject (6.5%). Six of them were males (60%), do not use face mask (80%), working years greater than 10 years (70%), smokers (60%), and BMI ≤25 kg/m2 (80%). There was a statistically significant relationship between age and COPD (p less than 0,05). Conclusion: Prevalence of COPD among street sweepers in Jakarta is 6.5%. Factor related to the occurrence of COPD is age.